Perlindungan Hukum Terhadap Korban Malpraktek Kedokteran - Iwan, Bintang R; Latupeirissa, Julianus Edwin; Saimima, Judy Marria (PATTIMURA Law Study Review, 2024)
ABSTRACT: Basic Legal Protection in the sense that errors can be intentional or negligent. Based on decision Number 75/Pid.Sus/2019/PN.Mbo, at the Cutt Nyak Dhien Meulaboh Regional General Hospital (RSUD) there were two health workers, namely a nurse and a midwife, who committed gross negligence. Namely injecting the wrong drug into a patient which results in death. Purposes of the research, to find out the legal regulations related to the behavior of medical personnel which causes the death of patients, and forms of criminal penalties for medical personnel who cause the death of patients, victims of medical malpractice and health protection laws. This research method uses a normative legal research type, while this research method uses a statutory approach, with data sources taken from secondary data obtained through library research. The data is then processed and carried out using qualitative analysis. Based on the results of the research, regulations regarding the activities of medical personnel that cause death are regulated in Articles 1 and 2 of Law Number 36 of 2014 concerning the Health of Medical Personnel. The law stipulates that actions of medical personnel that cause the death of a patient are punishable by imprisonment for a maximum of 5 (five) years. Criminal acts of medical personnel that result in the death of patients are acts of negligence by medical personnel, not intentional medical acts. It can be said that the defendant's actions were not only considered negligent, but the actions of the medical staff were also intentional, resulting in the death of the patient they were treating due to an error in administering the drug. Therefore, a sentence of 2 (two) years in prison is still deemed inappropriate and does not provide a sense of justice for the victim's family for the death of a patient who was a victim of professional misconduct, one of which was intentional.